SEMANTIC PROPERTIES OF CONSTRUCTION TERMS IN ENGLISH (Scientific journal of the Fergana State University, 2024)
This article analyzes the lexical and semantic category of terms related to the construction industry, the analysis of semantic relations in the study of terms of the construction industry, reveals the complex semantic relations between its components. This is a reflection of the hierarchical relationship between accepted words in this field. Therefore, we take the whole system of building terms as a lexical-thematic group, divide the relations of meanings that appear between its components into small groups, and describe the hierarchical relations between languages. The terms of house parts, reflection at a certain object level, have common typological characteristics due to the fact that they are attached to a single system of components that have developed in history, and depend on the accumulated experience of mankind. Therefore, all the peoples of the world have really developed the same system of concepts. This found its systematic reflection in the language of its speakers. The semantic relationship between the terms denoting the parts of the house shows that the English architectural features corresponding to the common signs of defining the parts of the house are significantly different in reality due to the special functional parts of the people's residential buildings and so on. dedicated to the problem of the specific features of the formation of terms in the field of construction.